1982
DOI: 10.1002/1097-0142(19820601)49:11<2420::aid-cncr2820491133>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed regional lymph node dissection in stage I melanoma of the skin of the lower extremities

Abstract: Results of a prospective randomized clinical trial conducted by the WHO Collaborating Centers for the Evaluation of Methods of Diagnosis and Treatment of Melanoma are reported. Five‐hundred‐fifty‐three Stage I patients whose limbs were affected entered the study; 267 were submitted to wide excision and immediate node dissection and 286 had wide excision and node dissection at the time clinically positive nodes were detected. Survival curves of the two treatment groups could be superimposed. No subsets of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(66 citation statements)
references
References 14 publications
2
60
0
3
Order By: Relevance
“…In a single study, early detection of occult metastatic disease in the draining lymph node basin by elective (prophylactic) lymph node dissection has been shown to increase survival when compared to therapeutic (delayed) lymph node dissection (Cascinelli et al, 1998). On the other hand, Veronesi presented a prospective randomized clinical trial conducted by the WHO in which patients with melanoma of the limb did not benefit from prophylactic lymph node dissection (Veronesi et al, 1982). This study was further supported by Sim, who also observed no significant difference with respect to overall survival and metastasis-free survival when patients were split into three different groups treated with WLE alone, WLE and 'immediate lymphadenectomy', or WLE and 'delayed lymphadenectomy' (Sim et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In a single study, early detection of occult metastatic disease in the draining lymph node basin by elective (prophylactic) lymph node dissection has been shown to increase survival when compared to therapeutic (delayed) lymph node dissection (Cascinelli et al, 1998). On the other hand, Veronesi presented a prospective randomized clinical trial conducted by the WHO in which patients with melanoma of the limb did not benefit from prophylactic lymph node dissection (Veronesi et al, 1982). This study was further supported by Sim, who also observed no significant difference with respect to overall survival and metastasis-free survival when patients were split into three different groups treated with WLE alone, WLE and 'immediate lymphadenectomy', or WLE and 'delayed lymphadenectomy' (Sim et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Giuliano e cols 4 , utilizando o mesmo sistema, associaram também substância radioativa (Tecnécio), que, aplicado na região tumoral, demonstrou a possibilidade de se identificar o sítio de drenagem inicial das neoplasias mamárias (linfonodo sentinela), permitindo o estudo prévio deste para a indicação ou não do esvaziamento axilar. A identificação do sítio preferencial de drenagem, que, quando não colonizado, tem se associado à ausência de neoplasia em todos os linfonodos do restante da cadeia 4,5 , reforça a posição de que é desnecessária a retirada de toda a cadeia nesta circunstância. Em relação ao câncer de mama a técnica é aplicada nos casos iniciais (estadios clínicos T1 e T2).…”
Section: Introductionunclassified
“…Entretanto, três ensaios clínicos randomizados não foram capazes de mostrar diferenças significativas de sobrevida em pacientes com LNS positivo submetidos à complementação do esvaziamento ganglionar. 44,45,46 Esses estudos foram discutidos por Balch, 47 destacando-se o fato de a maioria dos pacientes não ter realizado a cintilografia pré-operatória para confirmar a identificação correta da cadeia de drenagem. Esse dado é crucial quando se considera a alta freqüência de drenagem para mais de uma cadeia linfática ou para locais inesperados.…”
Section: Impacto Da Biópsia Do Lns No Estadiamento E Prognóstico Do Munclassified